Development of a regulatory testing procedure to study the metabolism of pesticides in farmed fish. Issue 2 (17th April 2015) - Schlechtriem, Christian; Bischof, Ina; Atorf, Cornelia; Bergendahl, Elena; Seymour, Paul; Whalley, Paul
Abstract: BACKGROUND: Diets used in commercial fish farming use significant proportions of crop‐derived commodities, and it is important to understand the potential for transfer of any pesticide residues on the crop into edible tissues in fish. It is a current requirement in the EU that fish metabolism studies must be performed when a pesticide is used in crops where commodities or processed fractions are fed to farmed fish. Fish metabolism studies in both rainbow trout and common carp have been carried out, following the new working document on the nature of pesticide residues in fish using 14 C‐labelled pesticide. RESULTS: The ingestion of experimental diets by rainbow trout and common carp resulted in the uptake and metabolism of the test item, as shown by liquid scintillation counting combined with radio‐thin‐layer chromatography. The metabolite profiles for trout and carp were qualitatively similar regarding the main residue. However, species‐specific differences were found regarding the remaining residue with rainbow trout showing additional metabolites in comparison to carp. CONCLUSIONS: Metabolism studies for regulatory purposes can be carried out with both fish species under laboratory conditions. The experimental design reported is suitable for quantifying the transfer of residues to edible tissues and enables characterisation of the chemical nature of residues. © 2015 Fraunhofer Institute for Molecular Biology and Applied Ecology (IME). Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.